Analisis Motivasi Volunteer Sport Tourism Paralayang di Nagari Malalo Kabupaten Tanah Datar Sumatra Barat - Fuji Anugrah Illahi (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2024)
Purpose: The study aims to determine the Motivation of Paragliding Sport Tourism Volunteers in Nagari Malalo, Tanah Datar Regency, which is contained therein. Method: This study used descriptive qualitative method. Data collected by conducting interviews with volunteers who participated in the TRoI III event committee in Nagari Malalo, Tanah Datar Regency, analytical techniques used data reduction, data presentation and data conclusions. As well as the validity of the data. Results: the results of the author's research can be concluded that the Motivation Analysis of Volunteeer Sport Tourism Paragliding in Nagari Malalo, Tanah Datar Regency where there are needs that must be met by volunteers, namely physiological factors, security factors, togetherness factors, self-esteem factors, pride factors. Contribution: The result of the research that the author conducted that the motivation of volunteers in Nagari Malalo, Tanah Datar Regency is that this paragliding event continues because this event can give birth to a volunteer spirit where they are sincere in doing it and this event can give birth to a spirit of togetherness that is exemplary for other nagari.